Constructing Community Identity and Local Wisdom Content in Regional TV Stations Digital Broadcasting - Lopulalan, Dortje L. Y.; Salakay, Selvianus; Sopacua, Yustina; Alfredo, Ronald (Fakultas Dakwah UIN Saizu Purwokerto, 2022)
This study analyzes Net TV Ambon and Indosiar Ambon as media that broadcast and show local content. The TV station show material with added value to explore the local wisdom, highlight cultural identity, and maintain its existence entering the digital broadcasting era. This study uses the qualitative approach and descriptive data as analysis methods. Data collection from research subjects was carried out using purposive sampling techniques. Primary data, namely the main data in the study, was conducted through in-depth interviews with informants, specifically KPID Maluku, KSP TV Indosiar Ambon, Liaison Officer Net TV Ambon, and local PH (Production House) in Ambon. Secondary data is obtained through reviewed impressions and various libraries from related sources. The results revealed that: 1) Net TV Ambon and Indosiar Ambon have the jargon